2016
DOI: 10.1371/journal.pone.0155163
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Different Mouse Wild Type Strains to Develop Diet-Induced NAFLD/AFLD-Associated Liver Disease

Abstract: Although non-alcoholic and alcoholic fatty liver disease have been intensively studied, concerning pathophysiological mechanisms are still incompletely understood. This may be due to the use of different animal models and resulting model-associated variation. Therefore, this study aimed to compare three frequently used wild type mouse strains in their susceptibility to develop diet-induced features of non-alcoholic/alcoholic fatty liver disease. Fatty liver disease associated clinical, biochemical, and histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 83 publications
7
45
0
Order By: Relevance
“…The vulnerability to HFD‐induced obesity was similar among the two groups probably due to the large hyperphagia shown by the dominant mice (Figure 3b,c). This finding in the C57BL/6J strain is at variance with previous data obtained in CD1 mice (Sanghez et al., 2013; Bartolomucci et al., 2009) thus suggesting a strain difference in metabolism (Fengler et al., 2016; Zou et al., 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The vulnerability to HFD‐induced obesity was similar among the two groups probably due to the large hyperphagia shown by the dominant mice (Figure 3b,c). This finding in the C57BL/6J strain is at variance with previous data obtained in CD1 mice (Sanghez et al., 2013; Bartolomucci et al., 2009) thus suggesting a strain difference in metabolism (Fengler et al., 2016; Zou et al., 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, phytol-diet alone greatly reduced hepatic triacylglyceride accumulation by 77% in WT males, and less so, by 52% in WT females (52). Because nonalcoholic fatty liver disease (NAFLD) is characterized by hepatic lipid accumulation, these studies suggested that the lower hepatic expression of FABP1, SCP-2, and SCP-x in WT females may make females more susceptible to NAFLD, correlating with high-fat-induced NAFLD in some strains of female (73), but not male, mice (74), as well as with the higher prevalence of NAFLD in women (74,75). Furthermore, phytol-diet made WT mice less susceptible to hepatic triacylglyceride accumulation, more so males than females and correlated with WT females having lower hepatic expression of FABP1, SCP-2, and SCP-x than WT males (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the strong positive association of age with hepatic steatosis in rodents and humans [20][21][22] , 30 week-old male C57BL/6J mice that transgenically express Ad36E4orf1 protein (E4orf1-Tg, n = 15) in the adipose tissue upon doxycycline induction 13 and age-matched wild-type (WT, n = 15) counterparts (Jackson Laboratory) were offered chow-doxycycline diet (chow-dox, 16% Kcal from fat, dox 600 ppm/kg) for 6 weeks followed by 10 weeks of HFdoxycycline diet (HF-dox, 60% Kcal from fat, dox 600 ppm/ kg). All animals were housed in the same room ≤5 mice/ cage on a 12-h light/12-h dark cycle, had ad libitum access to food, and received humane care.…”
Section: Experimental Design and Animal Modelmentioning
confidence: 99%